Decidual Control of Trophoblast Invasion: Mechanisms and Implications for Preeclampsia - Azam, Shazia; Musarrat, Sabeen; Sumaviya, Butt; Khushboo e Zehra; Basit, Abdul (Indus Journal of Bioscience Research, 2024)
Trophoblast invasion is essential for establishing a functional placenta and maternal-fetal exchange, regulated by the maternal decidua, which secretes both pro- and anti-invasive factors to balance trophoblast penetration into maternal tissues. Disruptions in this regulation are linked to pregnancy complications, particularly preeclampsia—a disorder marked by high blood pressure and impaired placentation due to insufficient trophoblast invasion. This study investigates the mechanisms of decidual control over trophoblast invasion and their implications for preeclampsia, utilizing clinical data from 50 patients at a tertiary care hospital in Karachi and an extensive literature review. We collected and analyzed blood and placental samples, quantifying cytokines, chemokines, and matrix metalloproteinases (MMPs) related to trophoblast function, and conducted patient interviews to assess psychosocial factors. Findings reveal elevated pro-inflammatory cytokines (e.g., IL-1β, IL-6) and chemokines, coupled with reduced MMP activity and increased tissue inhibitors, contributing to restricted trophoblast invasion. Interviews highlighted that stress, limited awareness, and healthcare access issues may compound biological risks in preeclampsia. These insights underscore the need for a multifaceted approach to managing preeclampsia, combining molecular and psychosocial interventions. Future research should aim to develop therapies targeting the molecular pathways that regulate trophoblast invasion while addressing social determinants to support maternal health and improve pregnancy outcomes.